2013
DOI: 10.1155/2013/958670
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Intravaginal Slingplasty versus Unilateral Sacrospinous Ligament Fixation in Treatment of Vaginal Vault Prolapse

Abstract: Objective. To investigate the differences in efficacy, postoperative complications, and patient satisfaction between posterior intravaginal slingplasty (PIVS) and unilateral sacrospinous ligament fixation (SSLF) procedures. Study Design. A retrospective study of thirty-three women who underwent PIVS or SSLF treatment for vaginal vault prolapse in Oulu University Hospital. The patients were invited to a follow-up visit to evaluate the objective and subjective outcomes. Median follow-up time was 16 months (range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…The UTI seen in patients in both groups (5 and 3 cases respectively) may be due to catheter insertion. Also in a study performed by Demirci et al, 7 UTI was found in 10% of cases 6 where sacrospinous fixation was done. And UTI was seen in one case in a study performed by Gupta.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The UTI seen in patients in both groups (5 and 3 cases respectively) may be due to catheter insertion. Also in a study performed by Demirci et al, 7 UTI was found in 10% of cases 6 where sacrospinous fixation was done. And UTI was seen in one case in a study performed by Gupta.…”
Section: Discussionmentioning
confidence: 92%
“…However, in a study performed by Demirci et al 7 , the operative time was 40.9 ± 28.3 minutes. The operative time was 53 (38-110) minutes in a study performed by Nyyssönen et al 6 Hemoglobin levels in both groups changed minimally, denoting minimal blood loss in all patients. But in a study done by Demirci et al, 7 the preoperative hemoglobin (Hb) level was 12.1 ± 1.8 gm/dL and postoperative Hb level was 10.0 ± 1.7 gm/dL.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Одним из распространенных поводов для данного оперативного вмешатель-ства является пролапс тазовых органов (ПТО). При этом данные литературы свидетельствуют о высокой вероятности выпадения купола вла-галища в послеоперационном периоде, дости-гающей 11,6-45 % [3,4].…”
Section: Introductionunclassified
“…Следует отметить, что больные с выпадением купола влагалища после перенесенной экстирпации/ампутации матки занимают особое место. Частота данного осложнения составляет от 11,6 до 45% [11]. По данным литературы, симптомы стресс-недержания мочи диагностируют у 38,6-70,1% женщин, нарушения дефекации развиваются более чем у 36,5% [1].…”
unclassified